Análisis del pib per cápita y coeficiente de gini del Ecuador en el periodo 2007 - 2017 - Sanchez Zavala, Jandry Daniel (Machala : Universidad Técnica de Machala, 2019)
This research work provides an analysis of economic growth its measurement, interpretation and use, as well as economic development studying the same parameters. The analysis is given of the macroeconomic indicators GDP per capita and the Gini coefficient which is a measure of the redistribution of wealth that is given in numbers from 0 to 1. For its development, it is taken into consideration the data calculated from the year 2007 up to data for the year 2017. Some economies maintain a priority to increase economic growth variables such as GDP, GDP per capita, budget deficit and other data that represent monetary amounts of income to the country. Sometimes over time these priorities take a capitalist bias since it tends to ignore the variables of economic development which give a diagnosis of the well-being of the population in a country, for this economic development analyzes the calculations of variables as coefficient of Gini, unemployment rate, illiteracy rate, mortality rate, among others that do not necessarily speak of economic income, in fact the majority presents as a unit of measurement the percentage, the percentage variation from one year to another or the proportion of the population total as the unemployment rate. The data and concepts of GDP per capita and the Gini coefficient in Ecuador from 2007 to 2017, its variations, behaviors, which are compiled in tables within the research and thus elaborate the appropriate graphics that facilitate the assimilation of the variables fulfilling in the best way the objectives proposed and pursued in this observation document. Recognize the factors that influence the changes of the macroeconomic variables studied among them can find economic policies such as fiscal policy with their public spending and trade policy with agreements that seek to improve the trade balance by increasing their exports. Establish the relationship that GDP per capita has with the Gini coefficient, looking for it by means of the statistical calculation, coefficient of correlation or Pearson coefficient, whose result would show if the behaviors of one can affect the behavior of the other over time. With all the analysis of the data provided by INEC and the World Bank, external actions or factors that influenced their variations explained in the conclusions of the objectives set out in this writing are established. The incidence that the GDP per capita had with the Gini coefficient with the correlation coefficient and the years in which the variations of these can be noticed simultaneously through graphics with standardized data. In the final part we appreciate the recommendations offered by the author in order to obtain an effective economy, prioritizing the guarantee that the population of Ecuador receives social benefits and not only that the country in general adapts its accounts in order to comply with expectations that are often raised or imposed by entities exogenous to the country.
El presente trabajo de investigación brinda un análisis del crecimiento económico su medición, interpretación y uso, además del desarrollo económico estudiando los mismos parámetros. El análisis se da de los indicadores macroeconómicos PIB per cápita y el coeficiente de Gini el cual es una medición de la redistribución de la riqueza que se da en números del 0 al 1. Para su desarrollo se toma en consideración a los datos calculados desde el año 2007 hasta los datos del año 2017. Algunas economías mantienen como prioridad incrementar las variables de crecimiento económico como es el caso del PIB, PIB per cápita, déficit presupuestario y demás datos que representen cantidades monetarias de ingreso al país. En algunas ocasiones a través del tiempo estas prioridades toman un sesgo capitalista ya que se tiende a ignorar las variables d desarrollo económico las cuales dan un diagnóstico del bienestar de la población en un país, para esto el desarrollo económico analiza los cálculos de variables como coeficiente de Gini, tasa de desempleo, tasa de analfabetismo, tasa de mortalidad, entre otras que no necesariamente hablan de ingresos económico de hecho la mayoría presenta como unidad de medida al porcentaje, la variación porcentual de un año a otro o la proporción de la población total como la tasa de desempleo. Se busca detallar los datos y conceptos del PIB per cápita y el coeficiente de Gini en el Ecuador dentro del periodo 2007 hasta el 2017, sus variaciones, comportamientos los cuales son recopilados en tablas dentro de la investigación y con ello elaborar lo adecuados gráficos que faciliten la asimilación de las variables cumpliendo de la mejor manera los objetivos propuestos y perseguidos en este documento de observación. Reconocer los factores que influyen en los cambios de las variables macroeconómicas estudiadas entre ellas se puede encontrar políticas económicas como la política fiscal con su gasto público y la política comercial con acuerdos que buscan mejorar la balanza comercial incrementando sus exportaciones. Establecer la relación que tiene El PIB per cápita con el coeficiente de Gini, buscándola por medio del cálculo estadístico coeficiente de correlación o coeficiente de Pearson, cuyo resultado demostraría si los comportamientos de una pueden afectar al comportamiento de la otra a través del tiempo. Con todo el análisis de los datos proporcionados por INEC y el Banco Mundial, se establecen acciones o factores externos que influyeron en sus variaciones explicados en las conclusiones de los objetivos planteados en este escrito. La incidencia que tuvo el PIB per cápita con el coeficiente de Gini con el coeficiente de correlación y los años en las que se puede notar las variaciones de estas de manera simultánea a través de gráficos con datos normalizados. En la parte final se aprecia las recomendaciones que ofrece el autor a fin de que se obtenga una economía efectiva, priorizando la garantía de que la población del Ecuador reciba beneficios sociales y no solo que el país en general adecue sus cuentas a fin de cumplir con expectativas que muchas veces son planteadas o impuestas por entidades exógenas al país.
Keywords: COEFICIENTE; GINI; DESARROLLO; ECONÓMICO